The level of infection and intensity of gastrointestinal nematode parasites in goats in Deli Serdang Regency, North Sumatra - Ulfa, Rasyida; Tanjung, Masitta; Nursal, Nursal; Hasan, Muhammad; Ferdian, Riyan (The Faculty of Veterinary Medicine of Syiah Kuala University, 2024)
Goats are one type of livestock that has a high socioeconomic value for farmers. Most of the goats owned by farmers in Amplas Village are grazed and penned. Goats that are kept in a semi-intensive way are annually attacked by diarrhoeal diseases compared to goats that are kept intensively. This is thought to be due to the presence of gastrointestinal parasites that attack livestock due to the way they are kept. The purpose of this study was to determine the level of infection and intensity of gastrointestinal nematode parasites in goats reared with semi-intensive and intensive rearing systems. The samples examined were 60 faecal samples which were divided based on the rearing system. The samples were then taken to the laboratory of the veterinary center in Medan. The results of the observations showed haemonchus, trichuris, and capillaria sp. The highest prevalence value in Haemonchus sp. was 100%. The lowest prevalence was in Capillaria sp. with a value of 3.3%. The highest intensity was for Haemonchus sp. parasites with a value of 358 grains/ind. The lowest intensity was for Capillaria sp. parasites with a value of 10 grains/ind.Keywords: parasite, nematode, gastrointestinal, goat